Time Cost Quality Trade-off Problems: A survey exploring the assessment of quality. (April 2018) - Orm, Mayassa Bou; Jeunet, Jully
Highlights: The paper surveys Time Cost Quality Trade-off Problems in a deterministic environment. The emphasis is on the definition of project activities quality. We propose a typology based on three main assessment of the quality of an activity. We report the absence of a direct relationship between quality and resources. Lexicographic optimisation has never been used. Abstract: Time Cost Trade-off Problems have received considerable attention in the literature on deterministic project scheduling problems but integrating the quality factor to these problems dates back to the mid-nineties with the pioneering work ofBabu and Suresh (1996) . Since then, to the best of our knowledge, about twenty papers have been published on this topic. The present paper analyses these Time Cost Quality Trade-off Problems in light of the usual classification for Time Cost Trade-off Problems that is based upon the number and category of resources and on the continuous or discrete type of the relationship between duration and cost or resources utilisation. In this survey, the emphasis is on the definition of project activities quality and on aggregation methods used to derive the overall project quality. We report the absence of a direct relationship between quality and resources allocated to activities and a lack of use of the lexicographic method to solve the problem.